SEBUAH KAJIAN TENTANG KEMAMPUAN SISWA TAHUN KEDUA DI SMAN 9 PEKANBARU DALAM MEMAHAMI TEKS-TEKS REPORT (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : The purpose of this study is to find out the second year students’ ability in comprehending report texts at SMAN 9 Pekanbaru. This research focuses on students’ comprehending report text in terms of factual information, finding main ideas, the meaning of vocabulary, identifying references and making inferences. The data were collected using report text test with multiple choice type. The test contained 25 items. The try out was conducted to check the validity and reliability of the test. Based on the research, it was found out that first: the ability of the second grade students in comprehending report text is in good level with the mean score of 72.0. Second, the students’ mean score in finding the factual information is in good level with the mean score of 71.3, in finding the main idea is in good level with the mean score of 74.4, in finding the meaning of vocabulary is in good level with the mean score of 71.0, in identifying references is in good level with the mean score of 71.7, and in making inference is also in good level with the mean score of 72.0. As a conclusion, the highest score among five components is in finding main idea, it is in 74.4 which considered as in good level. The lowest mean score is in finding the meaning of the vocabulary in context; it is in 71.0 which is considered also as in Good Level. Based on the result it can be inferred that students’ ability in comprehending report text of the second year students of SMAN 9 Pekanbaru is in Good Level.Keywords : Study, Ability, Report text.